2020
DOI: 10.15586/qas.v12i2.690
|View full text |Cite
|
Sign up to set email alerts
|

Effect of antioxidant extracted from bamboo leaves on the quality of box-packaged sturgeon fillets stored at 4 °C

Abstract: The effect of antioxidant extracted from bamboo leaves (AOB) on the quality of sturgeon fillets during chilled storage was examined via three parameters: total volatile basic nitrogen (TVB-N), pH and bacterial community composition. The samples treated with 0.05% (w/v) AOB exhibited the best quality, as evidenced by retarding both pH changes and the production of TVB-N. Pseudomonas and Aeromonas were the dominant indigenous bacteria present in fresh sturgeon fillets, whereas the presence of Janthinobacterium a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Antioxidant activity is a key property of active packaging films (Zhang et al, 2020). The antioxidant activity of the TS of QP film.…”
Section: Total Phenol Content and Antioxidant Activitymentioning
confidence: 99%
“…Antioxidant activity is a key property of active packaging films (Zhang et al, 2020). The antioxidant activity of the TS of QP film.…”
Section: Total Phenol Content and Antioxidant Activitymentioning
confidence: 99%
“…The daily dose of benzoic acid should not exceed 2000 mg. With the problems mentioned above, natural extracts such as chitosan, thymol, grape seeds, and lemon extracts have been used to extend the shelflife of pasta (Li et al, 2014). Again, Zhang et al (2020) also found that bamboo leaf extract can be used as a shelf-life extension ingredient. Peptide extracts have been shown to inhibit both Gram-positive bacteria and Gram-negative bacteria (Gasu et al, 2018).…”
Section: Molecular Weight Of Protein In Cplmentioning
confidence: 99%